Marché et régulation de l’intérêt général dans le secteur du transport routier de passagers : un débat rénové par l’activité des conducteurs - Liliana Cunha; Marianne Lacomblez (Activités)
This study analyses the working activity of drivers in the passenger land transport sector in the Metropolitan area of Porto. It considers the evolutions that follow a privatization policy and, namely, the changes at the level of work organization and the objectives which regulate this activity. Two cases have been object of a particular attention. In the first case, a bus route was selected on which three companies did business: a public company; another company which uses the route under analysis as a result of a concession attributed and controlled by the public company; and a third private company. In the second case, only one private bus company operated on the route. The final results of this research suggest that the companies’ policies are generally based, essentially, on market oriented options. On the other hand, the drivers try to balance these options with their own choices and solutions, which are based on values without dimension. The contribution of ergology enriched the reflexion on the strategies and renormalizations that workers make everyday, to establish operative trade-offs which make management of the activity’s objectives and the real needs of the users possible.